MICROTONAL INTONATION FROM COMPOSER’S, PERFORMER’S AND CONCERT-AUDIENCE’S PERSPECTIVE: THE CASE OF GYÖRGY LIGETI’S Hora lungă FOR VIOLA SOLO - Īvāne, Karlīna (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of this study is to explore the microtonal intonation, i.e., pitch lowered by a quarter-tone, in György Ligeti’s (1923-2006) „Hora lungă” for viola solo. It is examined from three points of view: composer’s, performer’s, and concert-audience’s. The artistic reasons for the use of microtonality in this piece were explored in Ligeti’s own and other written sources. The difficulties performer encounters hitting the microtonal pitch on viola (corresponding to the 11th harmonic in the overtone series) were investigated practicing the piece by the author of this paper herself. Two methods of practicing microtonal intonation were tested. Firstly, the out-of-tune (“false”) sounding pitch was searched by ear. Secondly, the validity of the second method – listening to harmonics of open C string was proofed, measuring pitch frequencies of open string harmonics in 16 recordings, including the author’s. Finally the perception of microtonal intonation by 26 subjects in live concert setting was tested. Pitch frequencies of performed excerpts were also analysed. Additionally, 17 subjects were interviewed about the perception of microtonal intonation. It was concluded that the appropriate way to practice microtonal intonation is to search the out-of-tune sounding pitch by ear, while other method – listening to open string harmonics, could be questionable as frequency measurements of harmonics showed that 11th harmonic deviated largely from the target. Perception test results have shown that both musicians and non-musicians were able to hear by a quartertone lowered pitch in the author’s performance. Frequency analysis has shown that microtonal intonation in the author’s performance was reliable. From answers in questionnaires and additional interviews it could be concluded that the composer’s intention to create the impression of a „strange, magical, nostalgic world” through the use of microtonal intonation worked, although it remains unclear, if the result would be similar without preparatory explanations before the interviews.